Effects of yeast combined with chromium propionate on growth performance and carcass quality of finishing steers - Vanbibber-Krueger, C. L.; Axman, J. E.; Gonzalez, John M.; Vahl, Christopher I.; Drouillard, James S. (My University, 2017)
A combination of yeast and chromium propionate (Y+Cr) was added to the diets of crossbred finishing steers (n = 504; 402 kg ± 5.76 initial BW) to evaluate impact on feedlot performance and carcass traits. We hypothesized supplementation of Y+Cr would increase growth of feedlot steers. Steers with initial plasma glucose concentrations ?6.0 mM were stratified by initial BW and randomly allocated, within strata, to receive 0 (control) or 3.3 g/d Y+Cr. Steers were further divided into heavy and light weight blocks with 6 pens/diet within each weight block. Cattle were housed in dirt-surfaced pens with 21 steers/pen and had ad libitum access to feed. Body weights were measured at 21-d intervals. Blood samples were collected on d 49 and 94 from a subset of steers (5/pen) for analyses of plasma glucose and lactate concentrations. At the end of the finishing phase, animals were weighed and transported 450 km to an abattoir in Holcomb, KS. Severity of liver abscesses and HCW were collected the day of harvest, and after 36 h of refrigeration, USDA yield and quality grades, LM area, and 12th rib subcutaneous fat thickness were determined. There were no treatment × time × weight block interactions (P > 0.05) and no treatment × block interaction for ADG, DMI, or final BW (P ? 0.06), but a treatment × block interaction (P = 0.03) was observed for G:F, in which control, light cattle had poorer efficiency compared with other groups. Treatment × weight group interactions were observed for overall yield grade and carcasses that graded yield grade 1 (P ? 0.04). Light steers supplemented with Y+Cr had decreased overall yield grade and increased percentage of carcasses grading yield grade 1 compared with their control counterparts, with no differences observed for heavy steers. Regardless of weight group, a greater percentage of carcasses from steers supplemented with Y+Cr graded yield grade 2 (P = 0.03) and fewer carcasses from steers supplemented Y+Cr graded yield grade 3 (P < 0.01) than control steers. No interactions or effects of treatment were detected for other carcass measurements (P ? 0.07). There were no treatment × weight group interactions or effects of treatment for plasma glucose or lactate concentrations on d 49 or 94 (P > 0.10). Overall, yeast in combination with chromium propionate may improve feed efficiency and decrease yield grade of light cattle but had no effect on remaining carcass traits and blood constituents. © 2016 American Society of Animal Science. All rights reserved.
Citation: Vanbibber-Krueger, C. L., Axman, J. E., Gonzalez, J. M., Vahl, C. I., & Drouillard, J. S. (2016). Effects of yeast combined with chromium propionate on growth performance and carcass quality of finishing steers. Journal of Animal Science, 94(7), 3003-3011. doi:10.2527/jas2016-0454
Keywords: Beef Cattle; Carcass Traits; Chromium Propionate; Glucose; Yeast